2007
DOI: 10.1007/s11255-007-9256-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of lemon and orange juices on calcium oxalate crystallization

Abstract: To investigate the inhibitory effect of lemon and orange juices on the growth of struvite crystals. Struvite crystals were grown by the single diffusion gel growth technique and the inhibitory effect of lemon and orange juices on the growth of struvitecrystals has been studied. With an increase in the concentration of lemon and orange juices, the weight of the formed crystals was gradually reduced from 2.49 g to 0.09 g (lemon juice) and 2.49 g to 0.21 g (orange juice) for the struvite crystals, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…In this experiment, approximately 30 min after mixing the calcium chloride and sodium oxalate solutions there was maximum increase in the optical density, which reflects the maximum crystal nucleation rate. After the solution reached equilibrium, the optical density became progressively lower, due to the diminished turbidity that resulted from the utilization of disperse particles in crystal aggregation [21]. In other words, decreased optical density was the outcome of enhanced crystal aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiment, approximately 30 min after mixing the calcium chloride and sodium oxalate solutions there was maximum increase in the optical density, which reflects the maximum crystal nucleation rate. After the solution reached equilibrium, the optical density became progressively lower, due to the diminished turbidity that resulted from the utilization of disperse particles in crystal aggregation [21]. In other words, decreased optical density was the outcome of enhanced crystal aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro effect of the copaiba leaf extract on the nucleation and aggregation of calcium oxalate monohydrate crystals was studied by using a previously described turbidimetric method [21]. Briefly, calcium oxalate monohydrate crystallization was obtained by mixing 12.5 mL calcium chloride (8 mmol/L) into 12.5 mL sodium oxalate (1 mmol/L) and sodium acetate/acetic acid buffer 10 mmol/L (pH 5.7).…”
Section: Methodsmentioning
confidence: 99%
“…This assay quantifies crystal nucleation and aggregation in metastable solutions of Ca 2+ and Ox. There are three parameters that characterize the crystallization process [36]: first, the maximum increase of optical density (OD) over time, termed S N , mainly reflects the maximum rate of formation of new particles and thus, represents crystal nucleation. Second, the rate of aggregation, S A , is derived from the maximum decrease in optical density.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary factors appear to affect the ability of urine to inhibit CaOx crystallization. In this regard, lemon juice has been found to inhibit the rate of crystal nucleation and aggregation [38,39]. Overall, the in vitro crystallization experiments confirmed that prophylaxis of renal stones could be achieved by reducing supersaturation through promotion of small crystal nucleates.…”
mentioning
confidence: 74%